ANALISIS DAYA DUKUNG LINGKUNGAN SEKTOR PERTANIAN BERBASIS PRODUKTIVITAS DI KABUPATEN BANGLI - Susanto, I Wayan (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract The agricultural sector has multi-functions covering the food production or food security aspects, the increase of farmer welfare or the eradication of poverty, and the preservation of life environment. The analysis of the supportability of the agriculture sector environment is using the land supportability approach based on land productivity, which is conducted by comparing between the supply and demand of land for the population in a certain region. By this method, the general description whether the supportability of land in a certain region is on surplus or deficit can be understood. The objective of research is to analyze the supportability of agriculture sector environment based on land productivity. The approach used in this research is quantitative descriptive, while the analysis tools used are: descriptive analysis; the analysis against the supply and demand of land based on the calculation method suggested by The Decree of The State Minister of Life Environment No.17 of 2009. The Result of this research indicates that the status of environmental supportability of Bangli District on 2011 is shown by land supply (SL) which reaches 167,947.58 Ha and land demand (DL) which attains 74,173.77. These figures are based on the land supportability approach that emphasizes on the land productivity in meeting the demand of biological product of the region. The comparison between land supply and land demand will facilitate the environmental supportability status, which is in the surplus category that is SL > DL.
Keywords: Keywords : land supply; land demand; environmental supportability status; productivity; agriculture sector.